Zakah, poverty alleviation, and inclusive growth in Nigeria (2016)
Macroeconomic literature is replete with discussions on fiscal policy in both developed and developing economies but not much research has been done on zakah, a compulsory tax on Muslims, especially its role in alleviating poverty and generating inclusive growth. Zakah primarily aims at taking surplus money or wealth from the comparatively well-to-do members of the Muslim society and give it to the destitute, the needy and the wayfarer, among others, to improve their purchasing power and economic prosperity. Thus, there is a need to investigate the impact of zakah on poverty alleviation and inclusive growth by assessing the nature of the nexus between zakah and poverty alleviation as well as how and the extent to which those assisted with zakah funds move out of poverty and contribute to inclusive growth. The paper uses descriptive statistics and ordinary least square regression and found that zakah can contribute to the empowerment of the recipients and can additionally alleviate the poverty of the poor who use the unconditional transfer for shelter, debt repayment, medical support, among others.